2014
DOI: 10.1016/j.neulet.2014.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress disrupts social behavior and prefrontal cortex parvalbumin interneurons at an earlier time-point in females than in males

Abstract: Early life stress exposure (ELS) yields risk for psychiatric disorders that might occur though a population-specific mechanism that impacts prefrontal cortical development. Sex differences in ELS effects are largely unknown and are also essential to understand social and cognitive development. ELS can cause dysfunction within parvalbumin (PVB)-containing inhibitory interneurons in the prefrontal cortex and in several prefrontal cortex-mediated behaviors including social interaction. Social behavior deficits ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
101
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 40 publications
3
101
0
1
Order By: Relevance
“…For example, sex differences in anxiety emerge from adolescence, with females more susceptible especially if they have experienced ELS (for review, see Bale and Epperson, 2015). Likewise, we found that ELS in mice predisposes to internalizing or externalizing behaviors in a sex-dependent manner, which may reflect differentially wired inhibitory circuitry in their prefrontal cortex (Z.Y., H.S.K., C.J., and T. K.H., unpublished observations;Holland et al, 2014).…”
Section: Sex-and Timing-based Vulnerabilities Of the Biological Impacmentioning
confidence: 58%
See 4 more Smart Citations
“…For example, sex differences in anxiety emerge from adolescence, with females more susceptible especially if they have experienced ELS (for review, see Bale and Epperson, 2015). Likewise, we found that ELS in mice predisposes to internalizing or externalizing behaviors in a sex-dependent manner, which may reflect differentially wired inhibitory circuitry in their prefrontal cortex (Z.Y., H.S.K., C.J., and T. K.H., unpublished observations;Holland et al, 2014).…”
Section: Sex-and Timing-based Vulnerabilities Of the Biological Impacmentioning
confidence: 58%
“…To address this, an alternative limited-bedding paradigm was initially developed in rats (Gilles et al, 1996), obviating the requirement for overt separation of pups and dams typically used in rodent ELS models . This paradigm induces inconsistent and fragmented maternal care (Heun-Johnson and Levitt, 2016), which has since been validated and adopted for use with mice by multiple laboratories Wang et al, 2011Wang et al, , 2013Gunn et al, 2013;Malter Cohen et al, 2013;Liao et al, 2014;Kohl et al, 2015;Naninck et al, 2015;Yang et al, 2015;Arp et al, 2016;Bath et al, 2016Bath et al, , 2017Liu et al, 2016;McIlwrick et al, 2016McIlwrick et al, , 2017Yam et al, 2017). The paradigm provides an ethologically relevant framework for addressing heritability of risk-, sex-, and developmentally dependent influences that determine outcomes following ELS.…”
Section: Neurobiological Signatures Of Windows Of Vulnerabilitymentioning
confidence: 99%
See 3 more Smart Citations